CELLULAR AUTOMATA AND COMPUTER GRAPHICS - Şen ÇAKIR; Aylin KANTARCI (Pamukkale University Journal of Engineering Sciences, 1999)
Cellular Automata (CA) are simple mathematical systems which provide models for a variety of physical processes. They show how minute changes and simple rules lead to enormous changes in the behaviour of a system. They can also be used as computer graphics tools to produce a rich reservoir of interesting figures. In recent years, CA have attracked the attention of many scientists. Today, CA are used in many fields from ecology to image processing. In this paper, it is shown that a large number of complex and interesting patterns can be created with relatively simple CA rules.